2021
DOI: 10.3389/fnagi.2021.625081
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Brain Function State During Mild Cognitive Impairment Based on Weighted Multiple Multiscale Entropy

Abstract: The mild cognitive impairment (MCI) stage plays an essential role in preventing the progression of older adults to Alzheimer's disease. In this study, neurofeedback training (NFT) is applied to improve MCI brain cognitive function. To assess the improvement effect, a novel algorithm called Weighted Multiple Multiscale Entropy (WMMSE) is proposed to extract and analyze the electroencephalogram (EEG) features of patients with MCI. To overcome the information loss problem of traditional multiscale entropy (MSE), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Of special interest is a large group of measures that are based on the concept of information entropy ( Bandt & Pompe, 2002 ; Costa et al, 2002 , 2005 ; Courtiol et al, 2016 ; Dávalos et al, 2019 ; Fadlallah et al, 2013 ; Inouye et al, 1991 ; Keshmiri, 2020 ; Kosciessa et al, 2020 ; Richman & Moorman, 2000 ; Y. Yin et al, 2016 ). Entropy measures have been helpful in psychophysiological studies of healthy subjects ( Fekete et al, 2021 ; Grady & Garrett, 2018 ; M. Liu et al, 2019 ; Mahjoory et al, 2019 ; Miskovic et al, 2019 ; Waschke et al, 2019 ), and growing evidence suggests that the measures can also be used to demonstrate a significant, progressive loss of entropy of neural activity in AD patients ( Ando et al, 2021 ; Echegoyen et al, 2020 ; Gómez & Hornero, 2010 ; Maturana-Candelas et al, 2019 ; Shumbayawonda et al, 2020 ; Su et al, 2021 ; W. Y. Yu et al, 2021 ). This suggests that measures of complexity or entropy could have potential as biomarkers for AD.…”
Section: Introductionmentioning
confidence: 99%
“…Of special interest is a large group of measures that are based on the concept of information entropy ( Bandt & Pompe, 2002 ; Costa et al, 2002 , 2005 ; Courtiol et al, 2016 ; Dávalos et al, 2019 ; Fadlallah et al, 2013 ; Inouye et al, 1991 ; Keshmiri, 2020 ; Kosciessa et al, 2020 ; Richman & Moorman, 2000 ; Y. Yin et al, 2016 ). Entropy measures have been helpful in psychophysiological studies of healthy subjects ( Fekete et al, 2021 ; Grady & Garrett, 2018 ; M. Liu et al, 2019 ; Mahjoory et al, 2019 ; Miskovic et al, 2019 ; Waschke et al, 2019 ), and growing evidence suggests that the measures can also be used to demonstrate a significant, progressive loss of entropy of neural activity in AD patients ( Ando et al, 2021 ; Echegoyen et al, 2020 ; Gómez & Hornero, 2010 ; Maturana-Candelas et al, 2019 ; Shumbayawonda et al, 2020 ; Su et al, 2021 ; W. Y. Yu et al, 2021 ). This suggests that measures of complexity or entropy could have potential as biomarkers for AD.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, although non-linear analysis is widely used in the characterisation of EEG changes throughout the process of cognitive decline [ 48 , 49 , 50 , 51 , 72 ], to the best of our knowledge, MSE has not been generally considered as an evaluation metric in previous NFT studies. That is, few NFT studies have applied MSE measurement in order to find NFT-induced EEG changes [ 52 , 75 ]. In fact, to our knowledge, there is only one study that reported the influence of classical NFT on EEG complexity in the elderly [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…That is, few NFT studies have applied MSE measurement in order to find NFT-induced EEG changes [ 52 , 75 ]. In fact, to our knowledge, there is only one study that reported the influence of classical NFT on EEG complexity in the elderly [ 52 ]. In this study, an increase in EEG complexity located in fronto-central region was shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data set used in this study is some of the clinical data reported by Su et al (2021) , including 26 subjects with aMCI with an average age of 65 years (60–70 years) and 20 HC subjects with an average age of 63.39 years (60–70 years). These aMCI patients were diagnosed by an experienced neurosurgeon and inclusion criteria included the Mini-Mental State Examination, Montreal Cognitive Assessment scores, and the Daily Living Test.…”
Section: Methodsmentioning
confidence: 99%